2021
DOI: 10.3389/fphar.2021.625074
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin D Rescues Deficits in Sexual Behavior and Ameliorates Neurological Dysfunction in Mice Exposed to Chronic Mild Stress

Abstract: Often associated with sexual dysfunction (SD), chronic stress is the main contributing risk factor for the pathogenesis of depression. Radix bupleuri had been widely used in traditional Chinese medicine formulation for the regulation of emotion and sexual activity. As the main active component of Radix bupleuri, saikosaponin D (SSD) has a demonstrated antidepressant effect in preclinical studies. Herein, we sought to investigate the effect of SSD to restore sexual functions in chronically stressed mice and elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In clinical applications, BR has been widely used for treatment of fever, pain, and inflammation associated with influenza or the common cold ( Yang et al, 2017 ). The modern pharmacological investigations reported that BR presented broad biological activities including anti-influenza ( Yan et al, 2022 ), anti-tumor ( Zhao et al, 2019 ; Zhou et al, 2021 ), anti-inflammation ( Jiang et al, 2020 ), anti-depression ( Guo et al, 2020 ; Chen et al, 2021 ), anti-stress ( Wang P. et al, 2021 ; Wang Z. et al, 2021 )and antipyretic ( Wang et al, 2019 ), antiviral ( Du et al, 2018 ), antimicrobial ( Liu et al, 2016 ), immunomodulatory ( Tang et al, 2021 ) and hepatoprotective effects ( Ren et al, 2019 ). Although different types of chemicals have been reported to contain in BCH (saponins, volatile oils, flavonoids and polysaccharides) ( Xing et al, 2015 ) and NCH (saponins, lignans, fatty acids, volatile oils and polysaccharides) ( Jiang et al, 2020 ), the saponins and volatile oils have been investigated to be the most important parts for both BR species which are associated to their antipyretic ( Xing et al, 2015 ; Li et al, 2018 ) and anti-inflammatory effects ( Kim et al, 2015 ; Ma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical applications, BR has been widely used for treatment of fever, pain, and inflammation associated with influenza or the common cold ( Yang et al, 2017 ). The modern pharmacological investigations reported that BR presented broad biological activities including anti-influenza ( Yan et al, 2022 ), anti-tumor ( Zhao et al, 2019 ; Zhou et al, 2021 ), anti-inflammation ( Jiang et al, 2020 ), anti-depression ( Guo et al, 2020 ; Chen et al, 2021 ), anti-stress ( Wang P. et al, 2021 ; Wang Z. et al, 2021 )and antipyretic ( Wang et al, 2019 ), antiviral ( Du et al, 2018 ), antimicrobial ( Liu et al, 2016 ), immunomodulatory ( Tang et al, 2021 ) and hepatoprotective effects ( Ren et al, 2019 ). Although different types of chemicals have been reported to contain in BCH (saponins, volatile oils, flavonoids and polysaccharides) ( Xing et al, 2015 ) and NCH (saponins, lignans, fatty acids, volatile oils and polysaccharides) ( Jiang et al, 2020 ), the saponins and volatile oils have been investigated to be the most important parts for both BR species which are associated to their antipyretic ( Xing et al, 2015 ; Li et al, 2018 ) and anti-inflammatory effects ( Kim et al, 2015 ; Ma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry assays were performed as previously described ( Wang et al, 2021b ), and mice were transcardially perfused with pre-cooled phosphate-buffered saline (PBS) and 4% paraformaldehyde. The brains were further fixed for 12 h at 4°C and dehydrated in 30% sucrose for cryoprotection.…”
Section: Methodsmentioning
confidence: 99%
“…CUMS was recently used to elucidate the role of projections from lateral habenula (LHb) to VTA in driving TST immobility, showcasing the construct validity of the paradigm ( Bergström et al, 2007 ; Cerniauskas et al, 2019 ). Changes in aggressive and sexual behaviour have been reported, but require further quantification ( Gronli et al, 2005 ; Couch et al, 2016 ; Chen et al, 2018 ; Wang et al, 2021 ). Another reported effect is the potentiation of escape deficits in the LH test ( Willner, 2005 ).…”
Section: Modelling Pathogenesismentioning
confidence: 99%